Games and business: human factors in gamified applications - LUIS FILIPE RODRIGUES; Oliveira, A.; Costa, C.; Rodrigues, H. (Advances in Human Factors in Wearable Technologies and Game Design. AHFE 2018. Advances in Intelligent Systems and Computing, 2018)
The user participation in the software development process is a key to improve the efficiency of business process, and more than likely, improve the user experience. This research aims to examine the users’ perceptions and expectations in the development of gamified applications. We outlined different categories of banking software to represent two types of software game analogies (soccer versus blackjack, respectively). Through user discussion, groups and a survey questionnaire with open questions. Content and thematic analyses, with Leximancer were used to analyse the text and to identify the key drivers of the gamified software. The findings from the textual analysis revealed themes (game, design, innovation, information, engagement, purchase, and analogy) that represents the gamification key drivers for software development in business. This is significant to understand the user’s perception about gamification to attract, retain, and user’s engagement.